Synthesis and Characterization of Ferrocenyl-N-heterocyclic Carbenes - Bechki, Lazhar; Lanez, Touhami (Asian Journal of Chemistry, 2010)
Carbenes containing ferrocenyl substituents are interesting target compounds due to the stereoelectronic influence of the ferrocenyl group in terms of steric protection, electron-donation and reversible redox chemistry. In this paper synthetic approaches to novel ferrocenyl-Nheterocyclic carbenes are summarized and their 1H NMR spectroscopic structural properties are discussed. The synthesis of these ferrocenyl-N-heterocyclic carbenes ligands involves the reaction of the alcohol 1-(ferrocenyl)ethanol successively with N-methylimidazol, N-butylimidazol and N,N-carbonyldimidazole in glacial acetic acid.